2023
DOI: 10.1177/07334648231175414
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving for Older Adults With Dementia During the Time of COVID-19: A Multi-State Exploratory Qualitative Study

Abstract: This qualitative semi-structured interview study explores how 64 family caregivers for older adults with Alzheimer’s Disease and related dementias across eight states experienced and executed caregiving decisions before and during the COVID-19 pandemic. First, caregivers experienced challenges communicating with loved ones and healthcare workers in all care settings. Second, caregivers displayed resilient coping strategies in adapting to pandemic restrictions, finding novel strategies to balance risks while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 678 , 679 , 680 , 681 In studies of dementia caregivers of relatives living in nursing homes or similar residential settings, caregivers indicated a number of challenges during the COVID‐19 pandemic, including severely limited contact with relatives due to visitation restrictions, a lack of transparent information and communication from care residences, fears of relatives dying alone and concerns about overburdened staff at care residences. 671 , 682 In addition, caregivers highlighted a number of resources and practices that were helpful during COVID‐19, including effective infection control measures adopted by care residences, robust communication with staff, and the need for creativity when remaining socially connected with relatives in nursing homes or similar residential settings. 671 There is also evidence of racial and gender differences in dementia care provision during the pandemic.…”
Section: Caregivingmentioning
confidence: 99%
“… 678 , 679 , 680 , 681 In studies of dementia caregivers of relatives living in nursing homes or similar residential settings, caregivers indicated a number of challenges during the COVID‐19 pandemic, including severely limited contact with relatives due to visitation restrictions, a lack of transparent information and communication from care residences, fears of relatives dying alone and concerns about overburdened staff at care residences. 671 , 682 In addition, caregivers highlighted a number of resources and practices that were helpful during COVID‐19, including effective infection control measures adopted by care residences, robust communication with staff, and the need for creativity when remaining socially connected with relatives in nursing homes or similar residential settings. 671 There is also evidence of racial and gender differences in dementia care provision during the pandemic.…”
Section: Caregivingmentioning
confidence: 99%
“…While not originally planned, the TLC app ended up including a fourth information module that provided caregivers with lists of respite ideas and activities that could be done in the home, oftentimes with the care-recipient present. These ideas were necessary and reflected the unique historical moment in which the TLC app was launched (late spring/summer of 2020), a time when many of the traditional respite providers as well as the informal arrangements made with friends and family to provide shared caregiving became unavailable because of the COVID-19 pandemic [48][49][50][51][52][53].…”
Section: Description Of the Tlc Interventionmentioning
confidence: 99%
“…People living with dementia are at high risk of depression, isolation, and behavioral changes, which may have been exacerbated by the COVID‐19 pandemic (Nakanishi et al., 2023 ). Prior studies have demonstrated that caregiver burden increased during the pandemic among informal caregivers of patients with PD (Hattori et al., 2023 ; Suzuki et al., 2021 ) and dementia in studies in India (Mukherjee et al., 2022 ), Thailand (Wongmek et al., 2023 ), Hong Kong (Fong et al., 2021 ), and across the United States (Mitchell et al., 2023 ; Yan et al., 2023 ). Caregiver burden increased in many regions of the world due to factors including aggravation of patient's symptoms, increased stress and anxiety, and needing to spend more hours at home given patients were less able to go out of the home during the pandemic (Carbone et al., 2021 ; Hattori et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%